Inhibition of Immune Checkpoints and Vascular Endothelial Growth Factor as Combination Therapy for Metastatic Melanoma: An Overview of Rationale, Preclinical Evidence, and Initial Clinical Data - Ott, Patrick A.; Hodi, F. Stephen; Buchbinder, Elizabeth I. (Frontiers in Oncology, 2015)
The role of angiogenesis as a mediator of immune regulation in the tumor microenvironment has recently come into focus. Furthermore, emerging evidence indicates that immunotherapy can lead to immune-mediated vasculopathy in the tumor, suggesting that the tumor vasculature may be an important interface between the tumor-directed immune response and the cancer itself. The advent of immune checkpoint inhibition as an effective immunotherapeutic strategy for many cancers has led to a better understanding of this interface. While the inhibition of angiogenesis through targeting of vascular endothelial growth factor (VEGF) has been used successfully for the treatment of cancer for many years, the mechanisms of its anti-tumor activity remain poorly understood. Initial studies of the complex relationship between angiogenesis, VEGF signaling and the immune system suggest that the combination of immune checkpoint blockade with angiogenesis inhibition has potential. While the majority of this work has been performed in metastatic melanoma, immunotherapy is rapidly showing promise in a broad range of malignancies and efforts to enhance immunotherapy will broadly impact the future of oncology. Here, we review the preclinical rationale and clinical investigations of combined angiogenesis inhibition and immunotherapy/immune checkpoint inhibition as a potentially promising combinatorial approach for cancer treatment.